Targeting 5-HT2B Receptor Signaling Prevents Border Zone Expansion and Improves Microstructural Remodeling After Myocardial Infarction. Issue 13 (30th March 2021) - Snider, J. Caleb; Riley, Lance A.; Mallory, Noah T.; Bersi, Matthew R.; Umbarkar, Prachi; Gautam, Rekha; Zhang, Qinkun; Mahadevan-Jansen, Anita; Hatzopoulos, Antonis K.; Maroteaux, Luc; Lal, Hind; Merryman, W. David
Abstract : Background: Myocardial infarction (MI) induces an intense injury response that ultimately generates a collagen-dominated scar. Although required to prevent ventricular rupture, the fibrotic process is often sustained in a manner detrimental to optimal recovery. Cardiac myofibroblasts are the cells tasked with depositing and remodeling collagen and are a prime target to limit the fibrotic process after MI. Serotonin 2B receptor (5-HT2B ) signaling has been shown to be harmful in a variety of cardiopulmonary pathologies and could play an important role in mediating scar formation after MI. Methods: We used 2 pharmacological antagonists to explore the effect of 5-HT2B inhibition on outcomes after MI and characterized the histological and microstructural changes involved in tissue remodeling. Inducible 5-HT2B ablation driven by Tcf21 MCM and Postn MCM was used to evaluate resident cardiac fibroblast- and myofibroblast-specific contributions of 5-HT2B, respectively. RNA sequencing was used to motivate subsequent in vitro analyses to explore cardiac fibroblast phenotype. Results: 5-HT2B antagonism preserved cardiac structure and function by facilitating a less fibrotic scar, indicated by decreased scar thickness and decreased border zone area. 5-HT2B antagonism resulted in collagen fiber redistribution to thinner collagen fibers that were more anisotropic, enhancing left ventricular contractility, whereas fibrotic tissue stiffness was decreased, limiting the hypertrophic response of uninjured cardiomyocytes. Using a tamoxifen-inducible Cre, we ablated 5-HT2B from Tcf21 -lineage resident cardiac fibroblasts and saw similar improvements to the pharmacological approach. Tamoxifen-inducible Cre-mediated ablation of 5-HT2B after onset of injury in Postn -lineage myofibroblasts also improved cardiac outcomes. RNA sequencing and subsequent in vitro analyses corroborate a decrease in fibroblast proliferation, migration, and remodeling capabilities through alterations in Dnajb4 expression and Src phosphorylation. Conclusions: Together, our findings illustrate that 5-HT2B expression in either cardiac fibroblasts or activated myofibroblasts directly contributes to excessive scar formation, resulting in adverse remodeling and impaired cardiac function after MI. Abstract : Supplemental Digital Content is available in the text.